Evaluating the Influence of Green Building Certifications on Construction Practices in Nigeria: A Systematic Review - Unegbu, Hyginus; Yawasa, D.S.; Dan-asabe, B.; Alabi, A.A. (Journal of Sustainable Infrastructure, 2025)
This research examines the influence of green building certifications on construction practices within Nigeria, concentrating on certifications such as LEED, EDGE, and BREEAM. Through a comprehensive review of literature spanning from 2015 to 2023, the study assesses the adoption of these certifications, the resulting changes in construction methodologies, and the economic and environmental impacts observed. The findings highlight a modest but increasing uptake of certifications, largely driven by adherence to international standards and emerging local efforts. In Nigeria, buildings that have achieved certification demonstrate notable advancements in energy efficiency, water use reduction, and waste management, contributing to greater sustainability and reduced operational expenses. Nonetheless, challenges such as substantial initial costs, a lack of adequately trained professionals, and insufficient governmental policies continue to impede progress. The research underscores the importance of enhanced governmental intervention, greater public education, and the growth of local industries focused on sustainable building materials. Upcoming research should explore the extended financial advantages of sustainable building methods, the challenges hindering their widespread implementation, and conduct comparative studies with other developing nations. This research provides important knowledge for policymakers, developers, and other key players dedicated to promoting eco-friendly building practices in Nigeria, aligning with international sustainability goals